2009
DOI: 10.1016/j.ydbio.2008.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of myoblast fusion on a cortical actin wall and nonmuscle myosin IIA

Abstract: Cell–cell fusion is a fundamental cellular process that is essential for development as well as fertilization. Myoblast fusion to form multinucleated skeletal muscle myotubes is a well studied, yet incompletely understood example of cell–cell fusion that is essential for formation of contractile skeletal muscle tissue. Studies in this report identify several novel cytoskeletal events essential to an early phase of myoblast fusion among cultured murine myoblasts. During myoblast pairing and alignment, cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 39 publications
0
62
1
Order By: Relevance
“…Importantly, a discrete actin-based structure associated with the fusion process in mammalian muscles is still missing. Indications that such structures may exist come from myogenic cell-culture studies (25,33), but have not been reported in vivo or in primary culture studies, and we were not able to identify them in the course of the current study.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, a discrete actin-based structure associated with the fusion process in mammalian muscles is still missing. Indications that such structures may exist come from myogenic cell-culture studies (25,33), but have not been reported in vivo or in primary culture studies, and we were not able to identify them in the course of the current study.…”
Section: Discussionmentioning
confidence: 87%
“…Visualization of the actin cytoskeleton revealed dynamic changes in fusing mouse myoblasts in vitro, as described for flies (Swailes et al, 2006;Duan and Gallagher, 2009;Nowak et al, 2009;Stadler et al, 2010). A dense actin wall forms in one cell, paralleling the long axis of aligned myoblasts (Duan and Gallagher, 2009), and is hypothesized to provide the membrane rigidity needed for cell fusion. As fusion proceeds, gaps appear in this actin wall at sites of vesicle accumulation, vesicles pair in both cells along the membrane, and fusion pores then form.…”
Section: Actin Cytoskeletal Remodeling In Mouse Myoblastsmentioning
confidence: 83%
“…siRNA knockdown of WASP and Vrp1 as well as Latrunculinmediated F-actin destabilization leads to a lower fusion index in C2C12 murine myoblast cell culture (Kim et al, 2007). In murine myoblast cell culture models, F-actin seems to play a role in the alignment of cells, and fusion pores have been suggested to appear in the actin-free regions (Duan and Gallagher, 2009), a suggestion also made by Kim et al (2007) for Drosophila myoblast fusion. Chen et al (2008) report for the viral fusogene gp64 that fusion pore expansion during syncytium formation in a cell culture assay is also restricted by an actin network, suggesting again a common mechanism.…”
Section: Functional Conservation Between Drosophila and Vertebrate Mymentioning
confidence: 87%